2019
DOI: 10.1021/acs.macromol.9b00699
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Partially Functionalized Phenylsilsesquioxane: [RSiO1.5]7[Me/nPrSiO1.5] and [RSiO1.5]7[O0.5SiMe3]3 (R = 4-Me/4-CN-Stilbene). Cage-Centered Magnetic Fields Form under Intense Laser Light

Abstract: Macromonomers [RPhSiO 1.5 ] 8,10,12 and [RCH CHSiO 1.5 ] 8,10,12 , where R is a conjugated group, have previously been shown to offer photophysical properties wherein excitation promotes an electron from the HOMO to an excited-state LUMO that sits in the center of the cage and allows communication between all conjugated groups, suggesting 3-D delocalization. In the current work, we explore replacing one conjugated group in [RPhSiO 1.5 ] 8 with either Me or nPr or s i m p l y r e m o v i n g o n e c o r n e r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 45 publications
1
36
2
Order By: Relevance
“…Our initial presumption was that these compounds should represent the limiting case where not only is there no 3D cage, but there are also two vinyl(Me/Ph)Si(O-) 2 bridges per cage in any oligomers/ polymers we might synthesize. Contrary to our original thoughts, the resulting compounds actually offer emission further red-shifted than any analogous compounds previously studied, [1][2][3][4][5][6][7]9] seeming to imply conjugation and semiconducting behavior where there should be none. In the following sections, we begin by characterizing a set of ladder copolymers and thereafter assess their photophysical properties.…”
contrasting
confidence: 97%
“…Our initial presumption was that these compounds should represent the limiting case where not only is there no 3D cage, but there are also two vinyl(Me/Ph)Si(O-) 2 bridges per cage in any oligomers/ polymers we might synthesize. Contrary to our original thoughts, the resulting compounds actually offer emission further red-shifted than any analogous compounds previously studied, [1][2][3][4][5][6][7]9] seeming to imply conjugation and semiconducting behavior where there should be none. In the following sections, we begin by characterizing a set of ladder copolymers and thereafter assess their photophysical properties.…”
contrasting
confidence: 97%
“…Our initial presumption was that these compounds should represent the limiting case where not only is there no 3D cage, but there are also two vinyl(Me/Ph)Si(O‐) 2 bridges per cage in any oligomers/polymers we might synthesize. Contrary to our original thoughts, the resulting compounds actually offer emission further red‐shifted than any analogous compounds previously studied, [1–7, 9] seeming to imply conjugation and semiconducting behavior where there should be none . In the following sections, we begin by characterizing a set of ladder copolymers and thereafter assess their photophysical properties.…”
Section: Methodscontrasting
confidence: 99%
“…offer photophysical properties not at all reflective of organic decorated silicas but commensurate with cage centered LUMOs. [1][2][3][4][5] We recently extended this concept of excited-state 3D conjugation to sets of incomplete and modified cages including corner-missing T 8 , [R'Stilbene-SiO 1.5 ] 7 [O 1.5 SiMe/nPr], [R'StilbeneSiO 1.5 ] 7 [O 0.5 SiMe 3 ] 3 , [6] and newly developed double decker (DD) [R'StilbeneSiO 1.5 ] 8 -[OSiMe 2 ] 2 and [R'StilbeneSiO 1.5 ] 8 [O 0.5 SiMe 3 ] 4 . [7] Recent efforts on double decker SQs follow two parallel paths in their development exploring either molecular or macromolecular hybrid materials.…”
mentioning
confidence: 99%
“…These redshifts reflect the formation of a cage-centered LUMO that allows excited state communication between all the appended moieties leading to 3-D conjugation suggesting semiconducting behavior. We recently reported that such LUMOs also form in SQs where one phenyl is replaced with Me/ n Pr or is completely removed (corner missing SQ) . These results suggest that 3-D LUMOs may form inside multiple types of SQ cage macromonomers, as recently also seen in germanium analogues …”
Section: Introductionmentioning
confidence: 57%